HUACAS LIMEÑAS: ANCESTROS AMAZÓNICOS Acerca de la presencia de pueblos del grupo etnolingüístico arawak en la costa central prehispánica a través de la toponimia - Vargas Nalvarte, Pedro Carlos (2017)
There ethnohistorical and archaeological evidence about various deities were worshiped in pre- Hispanic central coast. However, understanding their origin and details of worship is difficult because of the terse information and the absence of a suitable crossing from both sources. But now we have ethnographic studies with informants Yanesha village in the central jungle that show a fluid contact between coast and central jungle; this helps to understand the real dimension of apparently coastal planteadivinities; in turn, combining all the evidence is clear that the interaction between the Amazon and the central coast was more than just trade relations. Present evidence supporting the idea that at least two coastal divinities are as referring to Amazonian ancestors of Arawak groups and that there was a route between Ashaninka territory and the most famous coastal sanctuary : Pachakamak.